2019
DOI: 10.1016/j.amepre.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Applications in Weight Management: A Systematic Literature Review

Abstract: Context: Weight management is an effective strategy for controlling chronic disease and maintaining physical health, and research on this topic has risen dramatically over the past four decades. The present systematic literature review aimed to identify existing evidence on the efficacy of mobile health technology in facilitating weight management behaviors, such as healthy food consumption and physical activity. Evidence acquisition: A systematic search was conducted in Ovid MEDLINE and Ovid Psy-cINFO databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 66 publications
3
124
0
1
Order By: Relevance
“…There are thousands of weight loss and management apps but only a few have been tested in rigorous scientific trials [29,30]. However, in most cases software features, user experiences or actual outcomes have not been clearly reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are thousands of weight loss and management apps but only a few have been tested in rigorous scientific trials [29,30]. However, in most cases software features, user experiences or actual outcomes have not been clearly reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown improved body composition and cardiometabolic risk through ICT intervention [29,31]. In most cases, however, only short-term ( 6 months) weight loss with the intervention-induced weight loss of small clinical significance has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…While it is true that the boom in new technologies could be involved in the increased availability of energy dense and processed foods as well as the growing prevalence of sedentary behaviors, it is also true that they could play an important role in the management of health problems [8] Interventions based on new technologies could be easily developed and accepted for the management of weight disorders, since they represent an interesting tool to increase individuals' awareness of the quantity and quality of food consumed and the physical activity performed [9] Additionally, lifestyle mobile health (mHealth) self-monitoring [10] appears to have a greater effect on self-efficacy, patient motivation and adherence to treatment, in such a way that it may elicit a greater weight loss than conventional methods [11]. A recent systematic review concluded that mHealth applications may represent an effective strategy for weight loss, and, since the review included both observational and experimental studies, the authors called for an update, including a meta-analysis, when the number of intervention studies allowed for the pooled effect size (ES) of the effect of mHealth applications on weight loss to be estimated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Another key strategy that has been highlighted is the social validity of the application in question which revolves around the user's perception and response to the application ( 31 ). Levels of satisfaction and engagement are key measurement parameters.…”
Section: Qualitative Assessment Of Factors Influencing the Use Of Mobmentioning
confidence: 99%